Methods to analyse and interpret shallow seismic data: onshore central Perth basin, Western Australia - Esttaifan, Jamal Ohan Isteevan (Curtin University, 2015)
The main aim of the research was to develop a methodology for inferring complex sub-surface shallow structures from seismic data that are of a high relevance to hydrological studies in Perth Basin. A set of realistic 2D and 3D numerical modelling experiments were conducted that show that in the best case it is possible to interpret complex geological structure from 3D seismic data.